Initial Responsiveness to Reward Attainment and Psychopathology in Children and Adults: An RDoC Study. (July 2020) - Albert, Avery B.; Wagner, Kayla E.; Van Orman, Sarah E.; Anders, Kristin M.; Forken, Patricia J.; Blatt, Steven D.; Fremont, Wanda P.; Faraone, Stephen V.; Glatt, Stephen J.
Highlights: IRRA is significantly related to adaptive functioning in adults IRRA is significantly related to school, peer, and home functioning in children IRRA is less relevant to specific dimensions of psychopathology Abstract: The Research Domain Criteria (RDoC) initiative of the National Institute of Mental Health (NIMH) established a dimensional framework for understanding psychiatric constructs. Initial Responsiveness to Reward Attainment (IRRA) was identified as a dimensional construct relevant to several psychiatric disorders. The current study aimed to (1) examine IRRA as a predictor of psychopathology and impairment in children and their parents, and (2) examine the potential effects of sex and ancestry on the relationship between IRRA and psychopathology. Participants included 1127 children ages 6 to 12, and 1018 of their parents. Parents and children completed self-report measures of IRRA. Psychopathology and impairment were measured using self-report for adults, and parent-report and semi-structured interview for children. In adults, IRRA was significantly, but modestly, related to adaptive functioning. In children, IRRA was significantly, but modestly, related to overall, school, spare time, home, and peer functioning. Findings suggest IRRA may be a helpful construct for understanding adaptive functioning in adults and children, however it may be less helpful for understanding specific dimensions of psychopathology. Additionally, ancestry should be taken into consideration when examining how IRRA relates to psychopathology and functioning.